2018
DOI: 10.1016/j.apsb.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in topoisomerase-targeted cancer chemotherapy

Abstract: The DNA topoisomerase enzymes are essential to cell function and are found ubiquitously in all domains of life. The various topoisomerase enzymes perform a wide range of functions related to the maintenance of DNA topology during DNA replication, and transcription are the targets of a wide range of antimicrobial and cancer chemotherapeutic agents. Natural product-derived agents, such as the camptothecin, anthracycline, and podophyllotoxin drugs, have seen broad use in the treatment of many types of cancer. Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
131
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(150 citation statements)
references
References 101 publications
0
131
0
2
Order By: Relevance
“…Camptothecin derivatives (CPTs) such as topotecan, irinotecan and belotecan are common chemotherapy agents that are used for the treatment of cancers. These therapeutic agents are used either as monotherapy or in combination with other anticancer drugs for the treatments of small cell lung cancer, metastatic colon and rectal carcinoma [1,2]. Belotecan was recently approved in South Korea for non-small-cell lung cancer and ovarian cancer [2].…”
Section: Introductionmentioning
confidence: 99%
“…Camptothecin derivatives (CPTs) such as topotecan, irinotecan and belotecan are common chemotherapy agents that are used for the treatment of cancers. These therapeutic agents are used either as monotherapy or in combination with other anticancer drugs for the treatments of small cell lung cancer, metastatic colon and rectal carcinoma [1,2]. Belotecan was recently approved in South Korea for non-small-cell lung cancer and ovarian cancer [2].…”
Section: Introductionmentioning
confidence: 99%
“…We decided to focus on three synergistic drugs discovered in the screen: cabozantinib (receptor tyrosine kinase inhibitor), clofarabine (an RNR inhibitor) [36] and vinblastine (microtubule inhibitor/G2 arresting agent) [3740]. We also validated three drugs that demonstrated a significant loss of potency in cells lacking HDJ2: sorafenib (a VEGFR-2 inhibitor) [41], omacetaxine mepesuccinate (more commonly known as homoharringtonine, a protein translation inhibitor) [42] and idarubicin (topoisomerase II inhibitor) [43]. To determine synergy in a quantitative manner, we calculated drug synergy (Combination Index values, CI) between 116-9e and either synergistic or antagonistic drugs hits across a broad range of concentrations using the Chou-Talalay method [44].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, simultaneous blocking of both topoisomerase I and II showed synergies in all the patient samples. While this combination might provide an opportunity to effectively co-target AML rescue pathways, as inhibition of either of the enzymes alone may lead to increase in the expression of the other, hence resulting in treatment of resistance 24 , the sequential or simultaneous co-inhibition of topoisomerase I and II by compounds forming DNA lesions has shown severe side effects 60 . Therefore, dual inhibitors with a longer half-life and improved binding efficacy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Two such common combinations that showed high synergy (ZIP > 5) in the whole-well viability assay across all the samples included camptothecin (topoisomerase I inhibitor) combined with etoposide (topoisomerase II inhibitor), and venetoclax (Bcl-2 inhibitor) combined with vistusertib (mTOR inhibitor). While simultaneous blocking of both topoisomerase I and II may lead to overlapping toxicities 24 , it has been shown that co-targeting of both Bcl-2 and mTOR pathway triggers synergistic apoptosis and enhances drug-induced cytotoxicity by suppressing MCL-1 in leukemic cells 25 . The predictive approach also identified the ruboxistaurin-ipatasertib combination as synergistic in all but one sample (in the refractory AML3 sample the combination was additive with ZIP = 2.3).…”
Section: Patient-specific Combinations Show High Overall Synergy and mentioning
confidence: 99%